2023
DOI: 10.1088/1361-6528/acefd8
|View full text |Cite
|
Sign up to set email alerts
|

Growth kinetics and substrate stability during high-temperature molecular beam epitaxy of AlN nanowires

P John,
M Gómez Ruiz,
L van Deurzen
et al.

Abstract: We study the molecular beam epitaxy of AlN nanowires between 950 and 1215 °C, well above the usual growth temperatures, to identify optimal growth conditions. The nanowires are grown by self-assembly on TiN(111) films sputtered onto Al2O3. Above 1100 °C, the TiN film is seen to undergo grain growth and its surface exhibits {111} facets where AlN nucleation preferentially occurs. Modeling of the nanowire elongation rate measured at different temperatures shows that the Al adatom diffusion length maximizes at 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…The N and Sc fluxes were calibrated by determining the growth rate of GaN and ScN layers grown in N-limited and Sc-limited regimes, respectively. The temperature was calibrated as described in ref . GaN NWs were grown via self-assembly on sputtered TiN films decorated with Si seeds, as further described in ref .…”
Section: Methodsmentioning
confidence: 99%
“…The N and Sc fluxes were calibrated by determining the growth rate of GaN and ScN layers grown in N-limited and Sc-limited regimes, respectively. The temperature was calibrated as described in ref . GaN NWs were grown via self-assembly on sputtered TiN films decorated with Si seeds, as further described in ref .…”
Section: Methodsmentioning
confidence: 99%
“…The TiN is highly conductive and can be used as a bottom electrode for nanowire devices. Exact details of their growth and structural analyses were described elsewhere. ,, The N-polar GaN nanowires were grown on a highly doped n-type Si(111) substrate with a thin AlN buffer layer. In this case, a conductive Si substrate was used as the bottom contact of the nanowires.…”
Section: Methodsmentioning
confidence: 99%
“…This fact likely stems from the limited availability of AlN nanowires, whose synthesis is rather demanding . Recently, it was shown that high crystal quality and vertically aligned AlN nanowires can be achieved using plasma-assisted molecular beam epitaxy (PAMBE). , In this work, we implement such AlN nanowires in vertically integrated nanogenerator (VING) architecture and perform detailed investigations on their direct piezo-response characteristics, as well as evaluate their potential for mechanical sensing and energy-generating applications.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of GaN NWs on monocrystalline metallic substrates of proper crystallographic orientation solves the problem [ 24 ], but makes the whole fabrication procedure much more complicated. Interestingly, the high stability of metallic TiN buffers allowed the recent successful PAMBE growth of high-quality AlN NWs at an exceptionally high growth temperatures of ~1200 °C [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%